Solidarność Walcząca wobec transformacji ustrojowej - Brzechczyn, Krzysztof (Instytut Pamięci Narodowej, 2018)
This article contains a discussion of the political attitude of the Fighting Solidarity toward the concept of an agreement with communists concluded by the Independent Self-Governing Trade Union “Solidarity” led by Lech Wałęsa. The essay has the following chapters: 1. “The Political Thought of the Fighting Solidarity. An Attempt at an Overview”, 2. “The Predicted Fall of Communism”, 3. “The Fighting Solidarity and the Round Table Agreement”, 4. “The Fighting Solidarity and the Cabinet of Tadeusz Mazowiecki”. The Fighting Solidarity consistently opposed the conversations with communists which began in the fall of 1988 and did not like the idea of not registering the Independent Self-Governing Trade Union “Solidarity”, presented as a condition for the beginning of those conversations. During the proceedings of the Round Table, Morawiecki criticized the agreement to contractual elections, the creation of the position of a president with dictatorial rights, and the preservation of the influence of the nomenklatura in the army, the ministry of internal affairs, the judiciary, economy, administration, and culture. After the creation of the Cabinet of Tadeusz Mazowiecki, the Fighting Solidarity criticized the fact that key ministerial positions (the Ministry of National Defense, the Ministry of Interior and Administration) were taken by people nominated by the Polish United Workers’ Party. The organization also demanded that free elections to the parliament and local self-government should be organized. The Fighting Solidarity (later the Freedom Party) played a rather limited role in the political transformation. That was the case because the members and supporters of the Fighting Solidarity only participated in its activity in order to overthrow communism and not to gain power. After the parliamentary (1989) and presidential (1990) elections, many of them decided that that phase of the fight had finished so they withdrew from public activity to give more attention to their professional and family life. For that reason, the Freedom Party, a continuation of the Fighting Solidarity, had fewer human and material resources at its disposal and was marginalized by the main actors of the transformation. Both the Fighting Solidarity and the the Freedom Party offered critique – of the Polish Round Table Agreement, the selection of Wojciech Jaruzelski as a president, Mazowiecki’s “thick line” policy, the “enfranchisement of nomenklatura”, the Balcerowicz plan, and the presence of the Soviet army in Poland – and indicated a political alternative to the Polish people.
Keywords: Solidarność; Solidarność Walcząca; myśl polityczna; Okrągły Stół; transformacja ustrojowa; antykomunizm; historia PRL; upadek komunizmu